Influence of crucible material on the level of contamination in TiAl using induction melting - Barbosa, J. (2000)
This paper describes the processing results of TiAl alloys melted in a controlled atmosphere induction furnace, using crucibles made of graphite, calcia and zirconia stabilized with yttria, calcia and magnesia. Samples were poured into graphite permanent moulds or solidified and cooled inside the crucible, in order to simulate the worst case scenario in a metal/refractory reaction using this process. This paper presents segregation profiles of residual elements and their influence on the micro hardness of different phases and the extent of the “alphacase”.